Prevalence of ocular lesions in cattle from a Kansas sale barn - H.J. Davidson; Gerald L. Stokka; Tom Taul (Kansas Agricultural Experiment Station Research Reports, 1999)
This cross-sectional evaluation of cattle from a sale barn was completed to identify the prevalence of ocular lesions. A total of 100 cattle (91 cows and 9 bulls) was examined as they were being processed through a Kansas sale barn. Ocular lesions were found in 47%. The most frequently identified lesions were corneal scars, found in 26%. Although the exact cause of the scars could not be determined, they were similar in appearance to scars caused by infectious bovine keratoconjunctivitis (IBK) or pinkeye. The second most common lesion was squamous cell carcinoma (SCC), identified in 14%. Cataracts were identified in 7%. A white, raised, proliferative, optic nerve mass was identified in 11%. This high prevalence of eye lesions suggests that cattle frequently suffer from ocular disease or trauma. These lesions can be missed easily if the eye is not evaluated specifically during physical examination.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Eye; Ocular; Squamous cell carcinoma; Infectious keratoconjunctivitis; Cataract